CLASSIFICATION OF COLOR BLIND STUDENTS AT SMA NEGERI 1 LHOKSEUMAWE USING NAÏVE BAYES ALGORITHM - Rozzi Kesuma Dinata; Maryana; Sujacka Retno; Gadis Ayu Sofiana (Universitas Mulia, 2023)
This research aims to classify students and determine eye conditions with normal and partial color blindness by using Naïve Bayes algorithm. The research dataset was obtained from students at SMA Negeri 1 Lhokseumawe. The variables used in this research were 24 Plate Ishihara Tests with data collection techniques by using interviews, literature studies and questionnaires. Total data in this research are 140 data and divided into 110 training data and 30 testing data. The results showed that from 110 data trained, there were 69 students included in the normal group and 41 students included in the partial group. Then, the 30 testing data were tested into the classification system for color blind students using Naïve Bayes Algorithm. The accuracy level of the test results was 86.67% and 13.33% error.